Effect of the Automatic Needle Destroyer on Healthcare Providers’ Work in an Emergency Department: A Mixed-Methods Study - Kim, Su Min; Kim, Taerim; Lee, Jee Hyang; Cho, Sun Young; Cha, Won Chul (Healthcare informatics research, 2022)
Objectives: This study introduced a novel Automatic Needle Destroyer (AND) to an emergency department (ED) and assessed its effect on healthcare providers’ work.Methods: Between August and September 2019, in the ED of a tertiary hospital in Seoul, we conducted a mixed-methods study to evaluate the efficiency, safety, and usability of the AND using video analysis, surveys, and in-depth interviews, wherein participants described the advantages and disadvantages of the AND.Results: Compared to the existing method, introducing the AND significantly reduced the operating time from 2.32 ± 1.14 seconds to 1.77 ± 3.71 seconds (p < 0.001). The normal operation rate was 90.6%. The rate of needle-stick injuries (NSIs) and the mean system usability scale (SUS) showed no significant differences. The in-depth interviews indicated that the disadvantages of the AND were mostly operational. The advantages were related to profit, reduced direct contact with hazardous waste, and behavioral changes, such as not having to recap syringes.Conclusions: We introduced the AND to an ED environment, where NSIs occur frequently and many syringes are used, to evaluate its effect on providers’ work. The AND reduced the time for needle disposal, but the normal operation rate was low. No significant differences were found in the SUS score or the rate of NSIs. Although there are some restrictions on introducing the AND immediately, this study’s results showed its potential usefulness. Efforts to improve the operation of the device and a longer study period are needed to fully achieve safety and efficiency.